Step-by-step explanation:
Lets first find the remainder when p(x) is divided by x-2
p(2)=2(2)³+b(2)²+3(2)-5
p(2)=16+4b+6-5
p(2)=4b+17
Now let's find the remainder when q(x) is divided by x-2
q(2)=(2)³+(2)²-4(2)-b
q(2)=8+4-8-b
q(2)=4-b
Now let's equate both of them
4b+17=4-b
4b+b=4-17
5b=-13
b=-13/5 as required
P=1253(1+0.03)^6
P=1,253×(1+0.03)^(6)
P=1,496.15
Answer:
-816.8 ft²/min
Step-by-step explanation:
The rate of change of area is the product of the rate of change of radius and the circumference of the circle. At the time of interest, ...
dA/dt = C·dr/dt = 2πr·dr/dt
dA/dt = 2π·(26 ft)(-5 ft/min)
dA/dt = -260π ft²/min ≈ -816.8 ft²/min
Answer:
160
Step-by-step explanation:
10% of the candies is 16, and to get 100% from 10% is to multiply by 10.
So 10% *10 = 100%, then by association if 16 = 10%, then 16*10 will be the total 100%.
The correct question is
<span>Keiko sold 3 less than three-fourths of his sister’s sales. Which expression represents what Keiko sold?
Let
S----------------> </span><span>the amount that Keiko's Sister sold
</span>K----------------> the amount that Keiko sold
we know that
Keiko sold 3 less than three-fourths of his sister’s sales
K=(3/4)*S-3
the answer is
K=(3/4)*S-3